The Effect of Technology on Economy - Rojniruttikul, Nuttawut; Vajrapatkul, Adirek (My University, 2022)
This research aims to ingestigate the effect of technological progress on capital input. To meet the research objective, the simple closed economy DSGE model was constructed. The Bayesian technique is then employed to estimate the model parameters by using the quarterly detrended data of Thailand, which covers the period between 2001:Q1 and 2019:Q2, including GDP, policy rate, and employment. The result showed that technological progress can produce potential effects on major economic variables, namely labor, capital, price, return, consumption, and national income, and fits some previous studies. Therefore, government investment in technology and support for technology development should lead to economic growth.
Keywords: DSGE; macroeconomic variables; Technology progress; Thailand